Effect of Climate Change on Productive Traits and Genetic Parameters for Friesian Cows in Egypt - Ebrahim, Samah Z.; Genena, Shereen K.; Mostafa, Mohamed A. (Journal of Advanced Veterinary Research, 2023)
The database was obtained from 4560 records multiple records were collected from 2000 to 2022 For a total of 2560 records for Sakha station and 2000 records for El-Qardah station of the Ministry Agriculture and land reclamation in Egypt, meteorological data were obtained from the central laboratory of Agricultural climate. The data was divided into two periods, the period from 2000 to 2010 (P1) and the period from 2011 to 2022 (P2). Thermal Humidity Index (THI) and season effect on productive traits (LTMY, TMY, LP and DP) were between significant (P<0.05) and high significant (P<0.01) For both groups, except the effect of THI on the DMY in (P2) and season effect on DMY in (P1), which were non-significant. Climate change in the period from (2011 to 2022) witnessed a rise in temperature (AT) and was followed by an increase in relative humidity (RH) and atmospheric pressure (AP), as well as an increase in the value of THI especially the summer season, which is hotter than the rest of the seasons this had a negative effect on the productive traits. Estimates of permanent environmental variance for the second period for most traits were lower than additive genetic variance it may indicate that sensitivity to heat stress is not specific to the cow but is hereditary. Heritability estimates are low to moderate for most milk production traits show the possibility of improving genetically by selecting the most valuable cows for Heritability or genetic selection of cows and improving herd management.